Improvement of thermal comfort inside a mosque building - Noman, Fawaz Ghaleb (Penerbit UTM Press, 2016)
A combined natural ventilation and mechanical fans are commonly used to cool the interior space inside the mosques in Malaysia. This article presents a study on thermal comfort in the Al-Jawahir Mosque, located in Johor Bahru, Malaysia. The objective is to assess the thermal comfort inside the mosque under the present ventilation system by determining the Predicted Mean Vote (PMV) and the Predicted Percentage of Dissatisfied (PPD). These values were then compared to the limits stated in the ASHRAE Standard-55. It was found that the PMV varies from 1.68 to 2.26 while the PPD varies from 61 to 87. These show that the condition inside the mosque is quite warm. Computational fluid dynamics (CFD) method was used to carry out flow simulations, to identify a suitable strategy to improve the thermal comfort inside the mosque. Results of CFD simulations show that installing four exhaust fans above the windows on the west-side wall of the mosque is the most effective strategy to improve the thermal comfort inside the mosque. Both the PMV and PPD values can potentially be reduced by more than 60.